Pelatihan Pembuatan Sabun Cair Kesehatan Pada Kelompok PKK Kel. Katimbang Kec. Biringkanaya - Putri, Safridha Kemala; Nurhaedah, Nurhaedah; Zulkahfi, Zulkahfi; Sahabuddin, Sahabuddin; Malaha, Naomi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Antibacterial liquid soap is liquid soap formulated from soap ingredients and antiseptic herbal plants, betel leaves. The aim of this PkM activity is to provide training in making antibacterial liquid soap based on herbal plants to the PKK group, Katimbang Village, Biringkanaya District. The PkM method used is training, coaching and assistance in making antibacterial liquid soap. The results of the activity showed an increase in the average achievement of participants. These results show that public knowledge about making antibacterial liquid soap and how to make it has increased significantly. It is hoped that this increased knowledge of PKK women can be transmitted to the community of Katimbang Village, Biringkanaya District in general so that they can work together in improving community welfare and eradicating unemployment, especially in Katimbang Village, Biringkanaya District.